Role of Media Technology in Food Production, Kenya Vision 2030 - Eliud Garry Michura (Current Topics in Agricultural Sciences Vol. 6, 2022)
In the 21st Century, developing countries have shown higher human population growth compared to other centuries. And low food production leading to increased hunger and malnutrition. Lack of enough food production has many causes and one of the factors affecting farmers in food production is lack of solid and relevant information. The lack of clear policies on agricultural extension services has made it difficult for farmers to reach out for technical support in the field. The lack of extension services has alternatively created media forum to empower farmers through video sharing. Farmers are now adopting new methods of getting information that would help them achieve their goals in food production through media platforms. Such media platform which has succeeded in empowering farmers worldwide is video sharing. Access agriculture has developed programs which are now helping farmers with new technologies in improving food production particularly small scale farmers. The new innovation technology adoption makes farmers learn, share and watch demonstration videos from experts and other small scale farmers. After watching the videos, farmers are able to adopt easily what they have learnt. Access agriculture has produced simple videos produced in different languages and cultural context which can easily be understood by the farmers themselves living in any part of the globe. The agricultural media shows are made in a simplified content, less costly, quick and accessible to any farmer. The technology uses mobile phones which every farmer has. Internet accessibility, DVDs, Audio recordings and computers are some of the tools being used to enhance farmers’ concepts of smart agriculture. Kenya is currently experiencing a food deficit, and as a result, nearly 45 percent of the country’s population lives in poverty, with small-scale farmers accounting for the lion’s share. Farmer extension services and agricultural training colleges have dwindled over the years. The majority of small-scale farmers in rural areas face critical challenges in adopting new farming techniques that would otherwise increase food production. This paper examines the role of media technology innovation by Access agriculture in enhancing food production. The data examined in this paper was obtained from methodology Access agriculture data base, field observations from the small-scale farmers practice, desk top review and discussions with key informants in Kenya. The media platform technology has [played very significant role in empowering farmers and creating media platform sharing of information on the best agricultural practices that are now improving farmers’ skills and techniques leading to food solutions in Kenya. Sharing training videos has resulted in positive outcomes for more than half of Kenyan farmers. Most of the agricultural videos are communicating attractive and sexy information on agricultural demonstration techniques changing the perception and attitude of farmers particularly the young people who are now becoming more interested in farming hence increasing food production. The findings from this research study would be used to develop strategies that can farmers improve food production through young farmers who have the energy and sound technology to produce enough food for the Nation and beyond export.